An indicator framework to guide food system sustainability transition – The case of Sweden - Helena Hansson; Sarah Säll; Assem Abouhatab; Serina Ahlgren; Åsa Berggren; Elinor Hallström; Peter Lundqvist; U. Martin Persson; Lotta Rydhmer; Elin Röös; Pernilla Tidåker; Anna Winkvist; et al. (Environmental and Sustainability Indicators, 2024)
Well-aligned food policies are needed at both national and international level to guide food system transformation towards sustainability. Rigorous indicator frameworks are essential in order to facilitate discussion of priorities, enable comparisons, assessment and progress monitoring, and ensure accountability. In this study, we develop a national framework for a sustainable food system, using Sweden as a case. Our framework, the Food System Sustainability House, advances the literature on sustainable food system frameworks in three distinct ways. Firstly, it is tailored to a specific national context (Sweden in our case); secondly, it distinguishes between impacts of domestic production arising within territorial boundaries and impacts related to Swedish consumption independent of country of origin; and thirdly, to facilitate policy priorities, it suggests how different dimensions of sustainability are interlinked at a conceptual level. From a scientific perspective, the Food System Sustainability House postulates the interlinkages between the societal objectives of the food system, the environmental foundations on which production takes place, and the economic system and governance which in the framework are suggested to function as enablers for an overall sustainable system. From a policy perspective, the framework provides a much-needed basis for assessing food system sustainability by suggesting indicators within a comprehensive set of sustainability themes at national level for monitoring distinct perspectives. It also provides the necessary basis for a discussion on how sustainability dimensions are interlinked.